Crizotinib in Sarcomatous Malignancies Harboring ALK Fusion With a Definitive Partner(s): Response and Efficacy - Wu, Jinchun; Hu, Yongbin; Abdihamid, Omar; Huang, Gengwen; Xiao, Sheng; Li, Bin (Frontiers in Oncology, 2021)
Sarcoma or sarcomatoid malignancies are a set of mesenchymal-origin malignancies with vast heterogeneity in clinical and molecular characteristics. Anaplastic lymphoma kinase (ALK) tyrosine kinase is an oncoprotein, and Crizotinib is an effective adenosine trio-phosphate (ATP)-competitive ALK inhibitor. In this study, we summarized the data in the literature from 2010 to 2021 on Crizotinib in terms of its response, adverse events, and outcomes in sarcoma and sarcomatoid malignancies harboring ALK fusions with a definitive partner(s). Crizotinib is effective, however, surgery remains the mainstay of therapy, with newer evidence showing concurrent Crizotinib with surgery conferring long-term overall survival. However, we should still be cognizant of the heterogeneous landscape of Crizotinib efficacy and its associated fatal adverse events.